Pharmacological mechanisms of probenecid for SARS-CoV-2 and RSV co-infection: findings of system pharmacology, molecular docking, molecular dynamics simulation, and structure–activity relationship - Hong, Junbin; Guo, Zhendong; Huang, XiaoMei; Wu, Peng; Chen, Xinying; Liu, Xiaoyi; Yang, Jinghua; Lai, Yanni (Frontiers in Microbiology, 2025)
BackgroundThe clinical consequences of the co-infection with novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and respiratory syncytial virus (RSV) are not optimistic. Nevertheless, there is currently no approved therapeutic regimen specifically targeting SARS-CoV-2/RSV co-infection, with existing monotherapies showing limited efficacy. According to recent studies, probenecid has both anti-SARS-CoV-2 and anti-RSV effects. Therefore, as one probable molecular candidate for the co-infection with SARS-CoV-2 and RSV, probenecid was researched in this exploration.MethodsUsing systems pharmacology and bioinformatics, we characterized the targets associated with probenecid for the treatment of SARS-CoV-2/RSV co-infection, focusing on their biological functions, mechanisms and binding activities. To further validate these findings, we conducted molecular docking, MD simulations, electrostatic potential mapping, and SAR analysis to explore the binding interactions between probenecid and the identified core targets.ResultsWe identified 141 targets that overlapped with the co-infection and probenecid, and used these shared targets to construct a protein-protein interaction (PPI) network. Subsequently, we obtained the top 16 hub targets of probenecid for SARS-CoV-2/RSV co-infection, namely, AKT1, ALB, EGFR, CASP3, CTNNB1, SRC, HSP90AA1, and so on. According to the enrichment analysis, probenecid might affect inflammation, immunity, oxidative stress, and virus defenses; Toll-like receptor, TNF, IL-17, NOD-like receptor, cytokine-cytokine receptor, among others. Additionally, based on molecular docking analysis, probenecid is effectively bound to the targets related to the SARS-CoV-2/RSV co-infection. Meanwhile, according to molecular dynamics (MD) simulations and structure-activity relationship (SAR) analysis, we speculated that SRC and HSP90AA1 are more likely to be the target proteins of probenecid than the other proteins.ConclusionOur findings from systems pharmacology and bioinformatics analysis indicate that immune and inflammatory responses play a pivotal role in the therapeutic effects of probenecid. Infectious disease-related pathways also contribute significantly to its effectiveness in treating SARS-CoV-2/RSV co-infection. Further validation was conducted through molecular docking, MD simulations, electrostatic potential mapping, and SAR analysis. These analyses suggest that SRC and HSP90AA1 are the potential binding targets of probenecid. This study provides valuable preliminary insights into the molecular mechanisms of probenecid. It establishes a strong foundation for future research to explore its potential as a therapeutic strategy for SARS-CoV-2/RSV co-infection.